2021
DOI: 10.1371/journal.pone.0255045
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification on low-dose chest CT is an early predictor of severe progression of COVID-19—A multi-center, multi-vendor study

Abstract: Purpose Cardiovascular comorbidity anticipates severe progression of COVID-19 and becomes evident by coronary artery calcification (CAC) on low-dose chest computed tomography (LDCT). The purpose of this study was to predict a patient’s obligation of intensive care treatment by evaluating the coronary calcium burden on the initial diagnostic LDCT. Methods Eighty-nine consecutive patients with parallel LDCT and positive RT-PCR for SARS-CoV-2 were included from three centers. The primary endpoint was admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
5
0
1
Order By: Relevance
“…The consideration of sex as an independent predicting factor for death in COVID-19 patients remains controversial among researchers and clinicians. While some studies did not recognize sex as a risk factor for mortality 28 , 32 , 34 , 43 , 44 , others identified male sex as associated with higher odds of mortality in COVID-19 patients 26 , 42 , 45 . It is apparent that larger studies are necessary to reach a definite conclusion regarding the effects of sex differences on adverse outcomes in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The consideration of sex as an independent predicting factor for death in COVID-19 patients remains controversial among researchers and clinicians. While some studies did not recognize sex as a risk factor for mortality 28 , 32 , 34 , 43 , 44 , others identified male sex as associated with higher odds of mortality in COVID-19 patients 26 , 42 , 45 . It is apparent that larger studies are necessary to reach a definite conclusion regarding the effects of sex differences on adverse outcomes in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The summed score ranged from 0 to 12. This technique correlates with prognosis of patients with CAD and patients with COVID-19 [11] , [12] , [13] . For the first analysis patients were divided into two groups; the ‘no calcium’ group defined as a score of 0 versus the ‘calcium>0’ group.…”
Section: Methodsmentioning
confidence: 99%
“…Patients' coronary atherosclerosis burden can be estimated by assessment of coronary artery calcium (CAC), demonstrated by previous studies as a valuable prognostic factor in determining COVID-19 patients' survival [11] . They identified CAC as a high-risk marker for patients' prognosis and as predictor for admission to an intensive care unit [12] . CAC can be readily assessed on routinely performed computed tomography (CT) of the chest as well [13] .…”
Section: Introductionmentioning
confidence: 99%
“…CAC is a well-established biomarker used to identify individuals with subclinical coronary artery disease but at higher risk for cardiovascular events [ 13 ]. Some studies have shown that CAC volume is a predictor of in-hospital mortality of COVID-19 [ 8 ] or an independent biomarker for severe COVID-19 [ 9 11 ]. In the current issue of Hypertension Research [ 14 ], Cereda et al reported that a hypertensive status and CAC volume cutoff of more than 400 mm 3 could better stratify the clinical outcomes.…”
mentioning
confidence: 99%